THE EMERGENCE OF LEISURE TRAVEL AS PRIMARY PREVENTIVE TOOLS IN EMPLOYEE HEALTH BEHAVIOR - Antonia KINCZEL; Anetta MÜLLER (Geo Journal of Tourism and Geosites, 2023)
In our current modern world, it can be said that it is very difficult to live a balanced and healthy life, and to always perform well in the world of work, so it is very important to pay attention to our leisure time and our primary prevention activities, which can help preserve our health and improve our fitness. The purpose of the research is to examine the appearance of leisure tourist trips among employees, and how tourist trips appear among the primary prevention tools. Our research found answers to the main questions of what activities employees try to regain their ability to work, and whether trips are popular as primary prevention activities. The recreational activities of the employees are primarily filled by various obligations, but at the same time, the use of primary prevention activities is pushed into the background during everyday life. During the research, we established that medical and wellness holidays are very popular among the respondents, as 22.5% of the sample (133 people) take part in medical tourism holidays and 50.3% of the respondents (297 people) take part in health care on a focused wellness holiday. The quiet, calm environment and the closeness to nature, which helps the employees to regenerate, appeared prominently in the motivation for the choice of destination. Among primary prevention tools, leisure activities spent with family, relationships, and friends, healthy eating, and walking and nature walks are the ones that appear dominantly in the everyday life of employees. In order to reduce the problem of burnout, pressure to perform, and stress among employees and to enable them to perform well in their tasks, it is very important to assess their needs and provide them with programs that contribute to improving their health and regaining their ability to work, such as appropriate recreation programs and various trips.